Pengembangan Alat Model Pembelajaran Inkuiri pada Mata Kuliah Kalkulus Lanjut - La Moma; H Tamalene; Widya Putri Ramadhani (Jurnal Padegogik, 2021)
This study aims to develop learning tools that are relevant to the characteristics of students in the Mathematics Education Study Program. The development of the tools in this study used the Inquiry learning model in advanced calculus courses. Given the current situation in which the world and even Indonesia are being hit by the COVID-19 pandemic, all learning activities are carried out offline or online (in a network). These learning tools are designed to be used in online and offline learning situations. This type of research is development research, namely product development in the form of learning tools. There are 3 learning tools developed, namely Teaching Materials (BA), Student Worksheets (LKM) and Semester Learning Plans (RPS) which will be used in the teaching and learning process. The resulting learning tools are expected to help students in the learning process to improve their critical thinking, creative and problem-solving skills. The development of this learning tool consists of several phases, namely: (1) Difine, (2) Design, (3) Develop. This research has reached the definition and design stage.